“It’s a Boy Thing”: AAA Games Still Seem to Primarily Address Cisgendered White Male Players - Yun Zhang (Studies in Social Science & Humanities, 2024)
The boom in new technologies and the growth of the internet have contributed to the huge mainstream market for video games. However, despite the fact that video games have become mainstream, the stereotype that they are the exclusive domain of white male gamers persists, and those who do not fall into this category are still marginalised. This paper focuses on Crawford and Godbey’s 1987 framework for analysing the lack of representation of non-white and non-male video game players. In addition to this, some developers who are committed to developing diverse and inclusive game characters continue to fall short of addressing the root causes of marginalisation in video games.